Combination of resistance and aerobic exercise for six months improves bone mass and physical function in HIV infected individuals: A randomized controlled trial. (29th November 2020) - Ghayomzadeh, Morteza; Earnest, Conrad P.; Hackett, Daniel; SeyedAlinaghi, SeyedAhmad; Navalta, James Wilfred; Gholami, Mohammad; Hosseini Rouzbahani, Negin; Mohraz, Minoo; Voltarelli, Fabrício Azevedo
Abstract: To evaluate the effect of combined resistance and aerobic training (RT+AT) on regional bone mineral density (BMD) and physical performance in people living with HIV (PLWH). Forty PLWH (20 men and 20 women) were randomized into RT+AT group (n = 20; age = 38.3 ± 4.9) or non‐exercise control group (n = 20; age = 37.9 ± 5.1). The RT+AT group was required to perform a nonlinear periodized resistance training program targeting large muscle groups followed by 20 min aerobic exercise at 65‐80% of maximal heart rate. Participants in RT+AT performed three supervised sessions per week for 6‐months, whereas participants in the control group were instructed to continue with their current lifestyle habits. The primary outcome was bone mineral density (lumbar spine (L2‐L4), femoral neck, and distal 1/3 radius). Secondary outcomes included physical function, anthropometry, inflammatory markers, and growth factors. The RT+AT group demonstrated a significant increase in BMD at follow‐up for the Lumbar spine (L2‐L4), femoral neck, and 1/3 radius (all, P < .05), and There were no gender differences in the training response between men and women for any of the BMD regions. Similar findings were also observed for lean body mass, IGF1and Adiponectin ( P  < .001). We observed a decrease in percent body fat, fat mass, IL‐6, TNF‐α, and myostatin in the RT+AT group ( P  < .001). Finally, there was a significant increase in handgrip strength and gait speed for both women and men in the RT+AT group ( P < .001). A combination of resistance and aerobic training appears to be a feasible and effective means for counteracting bone loss and improving various inflammatory markers, physical function, and growth hormones in PLWH.